“God’s Field”: organisation and improvement of orthodox cemeteries of the 19th — beginning of the 20th centuries as reflected in church periodicals - Anna Bushuyeva (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2024)
The article analyzes the ideas of the Orthodox clergy about cemeteries related to their management, profitability, improvement, assessments of the state of this space, determined by the location of the cemetery in system of values, symbolic meanings and normative emotional models. The study revealed a contradiction between the appearance of the vast majority of urban and rural cemeteries and the idea of the clergy about the "proper" in this area. It was considered what was included in the concept of an “ideal cemetery” and what obstacles prevented the realization of this ideal: an inefficient administrative system, a lack of funds and enthusiasm from both the clergy and parishioners, especially in rural areas, as well as conflicting ideas about the attitude towards cemeteries in church ideology and in traditional folk culture, which was characterized by fear of the “unclean place” and the desire to avoid the dead, which was not typical for the clergy, better educated and professionally accustomed to the spectacle of ordinary death. In addition, the measures of the clergy to introduce the “correct order” of the organization of the cemetery space were studied: criticism of the inaction of the clergy, attempts to influence the priests through religious and value motivation and practical recommendations for bringing the appearance of the cemeteries in line with the “proper”; coupled with this, preaching to the people with various ways of argumentation and forms of emotional impact, including appealing to the idea of Christian virtue and duty, respect for dead ancestors and “kinship feeling”, arousing fear of possible punishment from above for neglecting the “holy place”, awakening national-confessional competitiveness.